The Impact of Climate Change on Natural Disasters in Slovenia - Hozjan, Karmen (Journal for Geography, 2015)
This article discusses the impact of climate change on natural disasters by statistical regions of Slovenia. We have presented the results of a statistical overview and calculated trends, average temperatures, precipitation and water balance, during the period of the past thirty years in Slovenia for selected meteorological stations. In the second part, we have statistically analysed individual natural disasters and cartographic representations, made with the help of a GIS tool, of estimated damages that were caused by natural disasters by statistical regions of Slovenia, during the period 2000–2013.